P63 Establishing the cost of hospitalised community acquired pneumonia (cap): a hospital episode statistics (hes) analysis. (15th November 2017) - Jones, D; Campling, J; Ellsbury, G; Czudek, C; Madhava, H; Slack, M
Abstract : Introduction: There are two types of pneumococcal vaccine available for adults: polysaccharide vaccine (PPV23) and a conjugate vaccine (PCV13). PCV13 vaccination is efficacious in adults aged 65 and over at preventing both invasive pneumococcal disease (IPD) and pneumonia caused by the serotypes in the vaccine 1 while the evidence is inconsistent for PPV23. 2, 3 The Joint Committee on Vaccination and Immunisation (JCVI) concluded that vaccination of ≥65 years with PCV13 was not cost-effective, and recommended against a national immunisation programme. As part of this analysis, a pneumonia admission (ICD-10 code J18) was costed at £715. 4 Aim: To obtain an alternative estimate of the cost of a hospitalised CAP both during the acute admission and following discharge. Materials and Methods: All patients aged ≥65 years with ICD10 J18 registered in HES between April 1 st 2014 and March 31 st 2015 were identified and their hospital-based activity tracked for 12 months. All in-patient, out-patient, and A and E attendances for these patients were extracted and the overall volumes and costs of these activities assessed over various timeframes. Costs were derived from the tariff via the Healthcare Resource Group codes. Results: The average cost of the initial in-patient (aged ≥65 years) admission for pneumonia (J18) was estimated at £3256. Over the 1–90 day period following the initial admission 69% of patients registered some additional utilisation of health care at an average cost of £2090. Conclusion: It is important that any cost effectiveness assessment accurately captures the costs averted by the intervention. Our analysis suggests that the cost of a pneumonia admission (J18) is 4-fold higher than that utilised in the 2016 analysis. In addition, significant additional costs may result from exacerbation of any underlying co-morbidities, thereby increasing the cost associated with a CAP infection. Even if only some of these additional costs were due to the original CAP infection, the value used in the original analysis significantly underestimated the cost of CAP. Please refer to page A258 for declarations of interest in relation to abstract P63. References: Bonten MJM, et al. N Engl J Med2015;372:1114–25. Moberley S, et al. Cochrane Database of Systematic Reviews 2013. Tin Tin Htar M, et al. PLoS ONE2017;12(5):e0177985. Van Hoek AJ, et al. PLoS ONE2016;11(2):e0149540.